Some remarks on change and innovation in ancient Near Eastern customary law - Fijałkowska, Lena (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The article presents the ways customary law could be gradually changed in the ancient Near East. They included working with existing institutions while modifying their consequences as well as their scope of application with tools such as legal fiction. However, the conservative nature of the ancient oriental culture, as well as that of the scribal education made any sudden, radical modification impossible, and even if a new contract type was created, it would keep the pretense of following a long-established practice.